1993
DOI: 10.1089/aid.1993.9.553
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death in AIDS-Related HIV and SIV Infections

Abstract: One of the difficulties in understanding the complex pathology of human immunodeficiency virus (HIV) infection is to explain the progressive depletion of the CD4 helper T cell population and consequently the destruction of the immune system. Although cytopathic effects of HIV are observed in vitro, they cannot in vivo account for CD4 T cell depletion because relatively few cells are productively infected. Thus immunological mechanisms must be envisaged. We have found that peripheral blood lymphocytes (PBLs) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
180
0
2

Year Published

1995
1995
2012
2012

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 313 publications
(198 citation statements)
references
References 33 publications
16
180
0
2
Order By: Relevance
“…Several studies have found that abnormal levels of apoptosis occur both in vitro [41][42][43][44][45][46][47][48][49][50][51] and in vivo 52,53 in CD4 þ and CD8 þ T cells from HIV-1-infected persons. Importantly, the majority of T cells undergoing apoptosis in HIV-infected patients are not infected by the virus; 52,53 this observation led to the definition of 'bystander' apoptosis when referring to apoptosis that is not occurring as a direct cytopathic effect of HIV.…”
Section: T-cell Apoptosis and Aidsmentioning
confidence: 99%
“…Several studies have found that abnormal levels of apoptosis occur both in vitro [41][42][43][44][45][46][47][48][49][50][51] and in vivo 52,53 in CD4 þ and CD8 þ T cells from HIV-1-infected persons. Importantly, the majority of T cells undergoing apoptosis in HIV-infected patients are not infected by the virus; 52,53 this observation led to the definition of 'bystander' apoptosis when referring to apoptosis that is not occurring as a direct cytopathic effect of HIV.…”
Section: T-cell Apoptosis and Aidsmentioning
confidence: 99%
“…1,2,[8][9][10] The third proposed mechanism is excessive, ongoing immune activation caused by a high, persistent viral antigen load and leading to the activation-induced death of various uninfected immune cells, including CD4 þ T cells. 1,2,4,8,9 Evidence for the involvement of indirect mechanisms of CD4 þ T-cell killing has been provided by the identification in vivo [11][12][13][14][15][16] and ex vivo [17][18][19] of increased number of dying, uninfected immune cells, including CD4 þ T cells, both in HIV1-infected persons and in non-human primate models of pathogenic simian immunodeficiency virus (SIV) infection, that are closely related to HIV. An important question is whether HIV1 may only cause death in activated, cycling CD4 þ T cells, or also in unstimulated noncycling CD4 þ T cells, which represent at any given time point the vast majority of the CD4 þ T cells in HIV1-infected persons.…”
Section: Introductionmentioning
confidence: 99%
“…Increased in vitro spontaneous, AICD and CD95/Fas-induced apoptosis have been reported in early studies. 26,27,30,31 The involvement of TNFR1 and TNFR2 in apoptosis of CD8 þ T cells from HIVinfected individuals was shown recently. 60 Furthermore, TNFrelated apoptosis-inducing ligand (TRAIL) can mediate in part AICD of CD4 þ and CD8 þ T cells.…”
Section: Apoptotic Defect Of Hiv-specific Cd8 þ T Cells Apoptosis Affmentioning
confidence: 96%
“…29 Early in vitro studies made apparent that both CD4 þ and CD8 þ T cells from HIV-infected individuals are sensitive to spontaneous apoptosis, activation-induced cell death (AICD) and CD95/Fas-mediated apoptosis. 27,[30][31][32][33] In vivo, this cell death occurs primarily in noninfected bystander cells and rarely in HIV-infected cells. 34,35 Furthermore, CD4 þ and CD8 þ T-cell apoptosis was detected in tonsillar tissues, 36 while a generalized apoptotic phenotype including also B cells and dendritic cells was observed in lymph nodes of HIV patients.…”
Section: Apoptotic Defect Of Hiv-specific Cd8 þ T Cells Apoptosis Affmentioning
confidence: 99%
See 1 more Smart Citation